Hubungan Antara Pembelajaran Studio Podcast dengan Perkembangan Keterampilan Berbicara Warga Belajar Program Kesetaraan di PKBM Think Indonesia School - Putri, Cindy Sefiana; Yulianingsih, Wiwin (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This study aims to analyze and identify the relationship between studio podcast learning activities and the development of speaking skills among learners in the equivalency program at PKBM Think Indonesia School. The study employs a sequential explanatory mixed-method approach, collecting both quantitative and qualitative data in two stages, with a primary emphasis on quantitative methods. Data collection techniques include questionnaires/surveys, observations, interviews, and documentation with learners in the equivalency program at PKBM Think Indonesia School. The results of this study indicate a positive and significant relationship between studio podcast learning and the development of speaking skills among learners in the equivalency program at PKBM Think Indonesia School, as evidenced by the calculated correlation coefficient (r) being greater than the tabulated correlation coefficient (0.617 > 0.361) with a significance value (sig) of 0.000 < 0.05. Furthermore, qualitative analysis through interviews with active participants in studio podcast learning demonstrates significant improvements and changes in speaking skills. Learners show progress in facial expression, pronunciation, intonation, and speaking ability through interaction with their learning teams and mentors, despite facing difficulties and showing perseverance in overcoming them through repeated practice.